Development and evaluation of the health belief model scale for exercise - Shiyan Wu; Xinglin Feng; Xinying Sun (Elsevier, 2020)
Objectives: This study was aimed to develop a health belief model scale for exercise among Chinese residents to describe the relationships between health beliefs and exercise for promoting residents to adopt or maintain exercise programs. Methods: Participants were from two projects, Project 1 with 3833 participants and Project 2 with 7319 participants. A pool of 21 items was developed based on a small-scale qualitative study about health beliefs of exercise and literature. Internal consistency and construct validity of the scale were evaluated with Cronbach's α coefficient, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and second-order confirmatory factor analysis. Results: A final version of 18 items loaded on six factors which could explain 60.30-% of variance was observed after EFA. The internal consistency of the final version with 18 items performed in Project 1 was acceptable (0.609). The reliability of the six subscales was good with Cronbach's α coefficient of 0.628, 0.713, 0.628, 0.801, 0.676 and 0.838 for perceived benefits, perceived objective barriers, perceived subjective barriers, self-efficacy, perceived severity and cues to action, respectively. CFA and second-order CFA indicated a good fit to data. Conclusions: The Health Belief Model Scale for Exercise(HBMS-E) is a valid and reliable instrument to assess health beliefs of exercise among residents in China. Understanding the health beliefs of exercise will help health professionals to develop effective interventions for health and evaluate the effectiveness.